EXPLORING THE LIVED EXPERIENCES OF INDIVIDUALS WITH SUBSTANCE USE DISORDER IN PAKISTAN: A QUALITATIVE STUDY ON IMPACTS, CAUSES, TREATMENT CHALLENGES, AND SOCIAL STATUS - Abrar Hussain Azad; Shahzad Ali Khan; Ijaz Ali; Usman Ghani; Hina Fatima; Pashma Wazir; Shaaray Abrar Umar (Journal of Ayub Medical College Abbottabad, 2024)
Background: Substance Use Disorder (SUD) presents a significant public health challenge globally, including Pakistan. Despite its high prevalence, there is limited research on the lived experiences of individuals with SUD in Pakistan, particularly in terms of cultural, social, and treatment challenges. Methods: This qualitative study explores the experiences of 60 male individuals with SUD in the capital territory of Pakistan. Participants were recruited using snowball sampling and were interviewed using a semi-structured guide covering various aspects of their lives impacted by SUD. Data were analyzed using thematic content analysis, with translation and back-translation processes ensuring accuracy in capturing participants’ narratives. Results: The study identified four main themes: the impact of SUD on individuals’ lives, causes of SUD, treatment experiences, and the social status of individuals with SUD. Participants reported significant financial and social hardships, strained interpersonal relationships, and severe physical and mental health issues. Causes of SUD included emotional distress, peer pressure, and abusive circumstances, while treatment options varied from medical interventions to spiritual healing. The stigma associated with SUD significantly impacted participants’ social reintegration and recovery. Conclusion: The findings highlight the complex interplay of socio-economic, psychological, and cultural factors influencing SUD in Pakistan. The study underscores the need for culturally sensitive, patient-centered approaches in the treatment and rehabilitation of individuals with SUD. Further research is needed to develop comprehensive strategies that address the specific needs of this population.